2019
DOI: 10.1037/prj0000335
|View full text |Cite
|
Sign up to set email alerts
|

Coherence between goals and therapeutic homework of clients engaging in recovery-oriented support.

Abstract: Objective: Our goal was to develop and pilot a methodology that could reliably identify therapeutic homework tasks that are coherent with the goals of individuals receiving mental health recovery support. Method: The content of goals and therapeutic homework tasks of 66 clients were classified using the Camberwell Assessment of Need Goal-Action Plan (CAN-GAP) taxonomy. Goal-homework pairs were considered coherent if the content of the homework and goal were both independently assigned the same content domain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The main advantage of this method was that it allowed access to the intervention from home. Participants in ICRP from home may have the possibility of rapid presence in the intervention, a strong, low-cost program, and training in the real world [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main advantage of this method was that it allowed access to the intervention from home. Participants in ICRP from home may have the possibility of rapid presence in the intervention, a strong, low-cost program, and training in the real world [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, multidisciplinary and integrated rehabilitation programs that lead to longer-term gains at the levels of activity and participation may highly impact cognitive symptoms through more efficient recruitment of brain regions [ 23 ], thereby positively influencing MS patients’ daily lives [ 24 ]. Moreover, the effectiveness of integrated cognitive rehabilitation programs should be more efficient for MS patients through homework intervention, making the content of the goals of these interventions and homework tasks more ecological [ 25 ]. The cognitive improvements observed after the implementation of homework interventions indicate that this personalized cognitive training could be a practical and valuable tool to improve cognitive skills [ 26 , 27 ] and additionally enhance neuronal plasticity in MS patients [ 27 ], which is associated with modifications of functional and/or structural plasticity within specific brain networks/regions involving cognitive functions [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Eleven studies evaluated collaboration and concordance between participant and practitioner perspectives regarding goal planning (Table 4). Seven of these studies were focused on the agreement between participant-identified goals, and the treatment plan developed or services provided (24,(68)(69)(70)(71)(72)(73), whilst one study reviewed the level of collaboration in goal planning (74), one assessed the individualization of written goals (75), one examined and compared the goal priorities of participants, families, and practitioners (76), and one reviewed the effectiveness of a collaborative training intervention for practitioners (77). Goal planning processes in rehabilitation programs (69,70,72,74,75), community-based mental health services (24,71,76), supported housing (73), and hospitals (68,77) were identified through existing treatment/rehabilitation plans (70,71,74,75,77), questionnaires (24,68,69,76), and interviews (72,73).…”
Section: Collaboration and Concordance In Goal Planningmentioning
confidence: 99%